Industry remotely operated vehicle imagery for assessing marine communities associated with subsea oil and gas infrastructure on the continental shelf of South-East Australia - Ierodiaconou, Daniel; McLean, Dianne; Birt, Matthew Jon; Bond, Todd; Wines, Sam; Glade-Wright, Ollie; Morris, Joe; Higgs, Doug; Whitmarsh, Sasha K. (Frontiers in Marine Science, 2023)
Introduction Offshore oil and gas (O & G) infrastructure provides hard substrata of structural complexity in marine environments and has been shown to have ecological value, particularly in oligotrophic environments. As infrastructure approaches end of life, understanding such values is critical to inform decommissioning decisions. Methods This study uses a decade of industry remotely operated vehicle (ROV) imagery to describe fish, invertebrate, and benthic communities on gas field infrastructure. Sampling was conducted over 22 km of flowline, three wells and one manifold in the temperate waters of Bass Strait, south east Australia in depths of 155 to 263 m. Results A total of 10,343 mobile animals from 69 taxa were observed. A higher diversity of fishes were observed on flowlines (28 taxa) compared to wells (19 taxa). Fish and invertebrate communities observed along flowlines were distinct from those observed on wells/manifold, however, there was also high spatial variability among the different flowlines surveyed and between the three wells and manifold. These differences appear to be driven by habitat and depth preferences of the species observed. Many sand-affiliated species were associated with buried sections of flowlines (Tasmanian giant crab Pseudocarcinus gigas, Balmain bug Ibacus peronii, slender sand burrower Creedia haswelli, red cod Pseudophycis spp., blue grenadier Macruronus novaezelandiae) whilst reef-associated and schooling species were observed on the wells/manifold (jackass morwong Nemadactylus macropterus, redbait Emmelichthys nitidus, splendid perch Callanthias australis). Species of ecological importance were also noted including the Australian fur seal (Arctocephalus pusillus doriferus), long-lived foxfish (Bodianus frenchii), and handfish (Brachionichthyidae spp). Discussion This study describes the habitat value of oil and gas infrastructure in a data poor temperate region that is important for understanding how the decommissioning of these structures may affect local marine ecosystems and fisheries. Therefore, it is critical to understand the habitat value of O&G infrastructure to marine life in the Bass Strait and whether decommissioning of these structures affect local marine ecosystems and fisheries. This study shows the complexity of determining temporal change in biodiversity values associated with these O & G structures from historical industry datasets that will be key for informing future decommissioning options. We also provide some guidance on how future quantitative data can be obtained in a systematic way using industry ROV data to better inform ecological investigations and decommissioning options.